Efektivitas Pembelajaran Menggunakan Youtube pada Mata Pelajaran Pemrograman Dasar Kelas X TK 1 SMK Negeri 3 Palangkaraya: Effectiveness of Learning Using You Tube for Basic Programming Subjects Class X Kindergarten 1 at State Vocational School 3 Palangkaraya - Sepriandani Sepriandani; Hendri Hendri; Muhammad Andi Setiawan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This study aims to: find out how the effectiveness of YOU TUBE in basic programming subjects for class X TKJ 1 in the current learning period at SMK Negeri 3 Palangkaraya. Data collection techniques in this study were observation, interviews, and documentation. Observations and interviews were conducted with 5 students of class X TKJ 1, 5 students, class teachers, and school principals. The results of the study show that: (1) students already understand and understand in using you tube and have no problems when using you tube. (2) most students can understand and understand the material presented when learning to use you tube. (3) most of the students really like and are comfortable when learning to use you tube and are enthusiastic about participating in learning so that the learning objectives can be achieved. Suggestions by researchers: (1) For school principals, it is hoped that they can be supervising teachers in the learning process. (2) Teachers are expected to be able to come up with creative and innovative ideas so that they are able to grow students' learning motivation so that it is always maintained and improved to support student learning activities to be more harmonious and effective. (3) For students, it is expected to be able to increase concentration and motivation during teaching and learning, because the material provided by the teacher needs to be digested and understood as knowledge that can be useful for a bright future.